Predication Reservoir Parameters of Pressure Transient Analysis with an Alternative of Temperature Transient Analysis - Badron, Hafiz Adri (Universiti Teknologi Petronas, 2011)
This project is about "Predication Reservoir Parameters of Pressure Transient Analysis with an Alternative of Temperature Transient Analysis by Using PanSystem Simulator". The background of this project and its objectives is to study Pressure and Temperature Transient Analysis. In this project, the scope of study will be focusing on well testing not only in Pressure Transient Analysis but also in Temperature Transient Analysis. In doing this interpretation, the author will be using a well testing simulator called PanSystem from Weatherford. The beauty of Pansystem will also be described in this report. He compares the result from PanSystem to another simulator, which is Saphir with the input data used is the same and the finalized model is identical. The purpose of this study is to be able to use the well testing software and do the interpretation and analysis from it. And once this is achieved, the results from the interpretation will the findings, which is the ultimate objective of the project which is to predict reservoir parameters.